E-COMMERCE SECURITY: LEGAL AND POLICY ASPECTS OF TECHNOLOGY SOLUTIONS IN UZBEKISTAN (Archive of Conferences, 2020)
Electronic commerce is an integral part of the economy of our century, ensuring the exchange of economic information between business entities on the basis of modern information technologies. Its development is transforming the modern economy into a virtual economy, as a result of which the efficiency of business communications is increasing. Experts around the world predict that the role of e-commerce in the economy will continue to grow and become an important sector in the future